Box–Behnken design to determine optimal fermentation conditions for apple-fortified mulberry wine using Saccharomyces bayanus : - THUY, Nguyen Minh; TIEN, Vo Quoc; GIAU, Tran Ngoc; HAO, Hong Van; THANH, Nguyen Van; THANH, Nguyen Ngoc; TAI, Ngo Van; DANG, Pham Cam; MINH, Vo Quang (Food Science and Technology, 2023)